FVTF inhibits hepatocellular carcinoma stem properties via targeting DNMT1/miR-34a-5p/FoxM1 axis - Xiao-Cheng Cao; Jinwu Peng; Ye-Bei Qiu; Wei Zhu; Jian-Guo Cao; Hui Zou; Zheng-Zheng Yu; Di Wu; Shan-Shan Lu; Wei Huang; Hong Yi; Zhi-Qiang Xiao (Chinese Medicine)
Abstract Background Fructus Viticis Total Flavonoids (FVTF) is a novel candidate preparation that possesses anticancer activity. However, the role and mechanism of FVTF-inhibiting human hepatocellular carcinoma (HCC) cell stem properties is unclear. Methods Liquid chromatography (LC) in conjugation with mass spectrometer (MS) was used to identify the compounds of FVTF. Tumorsphere and soft agar colony formation ability, cancer stem marker expression levels, CD133+ cell percentage, and a xenograft model were utilized to investigate the impact of FVTF on HCC cells stemness. PCR array and qRT-PCR were conducted to identify differentially expressed cancer stem-related genes and miRNAs between FVTF-treated and untreated HCC cells, respectively. Pyrosequencing was conducted to assess the DNA methylation level of the miR-34a-5p promoter. A luciferase reporter assay was performed to verify whether FoxM1 serves as a direct target of miR-34a-5p. Additionally, immunohistochemistry of an HCC tissue microarray was carried out to assess the expression levels of DNMT1, FoxM1, and miR-34a-5p. Results A total of 26 compounds, including 10 flavones, in FVTF were identified. FVTF significantly reduced the ability of tumorsphere and soft agar colony formation, the levels of CD44 protein and BMI1, OCT4 and SOX2 mRNAs in HCC cells, and in vivo tumor initiation ability of HCC cells. Mechanistically, FVTF inhibited HCC cell stem properties via targeting DNMT1/miR-34a-5p/FoxM1 axis. Clinically, DNMT1 expression was inversely correlated with miR-34a-5p expression, whereas a positive correlation was noted between DNMT1 and FoxM1 expression levels, and high DNMT1 levels, low miR-34a-5p levels, and high FoxM1 levels were associated with cancer recurrence. Furthermore, a combination of DNMT1, miR-34a-5p and FoxM1 served as an independent prognostic indicator influencing both DFS and OS in patients with HCC. Conclusions FVTF inhibits HCC cell stem properties by targeting DNMT1/miR-34a-5p/FoxM1 axis, which is associated with HCC recurrence and prognosis, and FVTF is a prospective treatment drug for human HCC.